Lack of transgene and glyphosate effects on yield, and mineral and amino acid content of glyphosate‐resistant soybean. Issue 5 (8th August 2017) - Duke, Stephen O; Rimando, Agnes M; Reddy, Krishna N; Cizdziel, James V; Bellaloui, Nacer; Shaw, David R; Williams, Martin M; Maul, Jude E
Abstract: BACKGROUND: There has been controversy as to whether the glyphosate resistance gene and/or glyphosate applied to glyphosate‐resistant (GR) soybean affect the content of cationic minerals (especially Mg, Mn and Fe), yield and amino acid content of GR soybean. A two‐year field study (2013 and 2014) examined these questions at sites in Mississippi, USA. RESULTS: There were no effects of glyphosate, the GR transgene or field crop history (for a field with both no history of glyphosate use versus one with a long history of glyphosate use) on grain yield. Furthermore, these factors had no consistent effects on measured mineral (Al, As, Ba, Cd, Ca, Co, Cr, Cs, Cu, Fe, Ga, K, Li, Mg, Mn, Ni, Pb, Rb, Se, Sr, Tl, U, V, Zn) content of leaves or harvested seed. Effects on minerals were small and inconsistent between years, treatments and mineral, and appeared to be random false positives. No notable effects on free or protein amino acids of the seed were measured, although glyphosate and its degradation product, aminomethylphosphonic acid (AMPA), were found in the seed in concentrations consistent with previous studies. CONCLUSIONS: Neither glyphosate nor the GR transgene affect the content of the minerals measured in leaves and seed, harvested seed amino acid composition, or yield of GR soybean. Furthermore, soils with a legacy of GR crops have no effects on these parameters in soybean. © 2017 Society of Chemical Industry Abstract : No effects of the glyphosate‐resistance transgene or glyphosate were found on mineral and amino acid content or yield of glyphosate‐resistance soybeans.